The Use of a Knowledge Translation Program to Increase Use of Standardized Outcome Measures in an Outpatient Pediatric Physical Therapy Clinic: Administrative Case Report. Issue 4 (1st April 2015) - Schreiber, Joseph; Marchetti, Gregory F.; Racicot, Brook; Kaminski, Ellen
Abstract : Background and Purpose: Pediatric physical therapists face many challenges related to the application of research evidence to clinical practice. A multicomponent knowledge translation (KT) program may be an effective strategy to support practice change. The purpose of this case report is to describe the use of a KT program to improve the knowledge and frequency of use of standardized outcome measures by pediatric physical therapists practicing in an outpatient clinic. Case Description: This program occurred at a pediatric outpatient facility with 1 primary clinic and 3 additional satellite clinics, and a total of 17 physical therapists. The initial underlying problem was inconsistency across staff recommendations for frequency and duration of physical therapist services. Formal and informal discussion with the department administrator and staff identified a need for increased use of standardized outcome measures to inform these decisions. The KT program to address this need spanned 6 months and included identification of barriers, the use of a knowledge broker, multiple workshop and practice sessions, online and hard-copy resources, and ongoing evaluation of the KT program with dissemination of results to staff. Outcome measures included pre- and post-knowledge assessment and self-report surveys and chart review data on use of outcome measures. Outcomes: Participants (N=17) gained knowledge and increased the frequency of use of standardized outcome measures based on data from self-report surveys, a knowledge assessment, and chart reviews. Discussion: Administrators and others interested in supporting practice change in physical therapy may consider implementing a systematic KT program that includes a knowledge broker, ongoing engagement with staff, and a variety of accessible resources.